Role of Visual Assessment of High-Quality Cakes in Emotional Response of Consumers - Jose Alba-Martínez; Andrea Bononad-Olmo; Marta Igual; Luís M. Cunha; Javier Martínez-Monzó; Purificación García-Segovia (Foods, 2022)
Thinking of the present gastronomic trends is inevitable when talking about innovation in haute pastry. Launching a successful product that meets consumers’ high expectations despite the rising demand for new creations is increasingly complex. For this reason, sensory analysis studies are more and more interested in studying the emotional response evoked by these products to better understand and improve user experiences. The main goal of this work was to conduct a study to analyze the emotional arousal of consumers after the visualization of five haute patisserie cakes. An online questionnaire with the EsSense Profile® scale and CATA methodology were used for data collection. The EsSense Profile® is a predefined and validated scale that measures food-related emotions, which includes 39 terms. When analyzing the emotions expressed by all the participants, 22 were statistically significant, of which 14 were classified as positive, 6 as neutral, and only 2 were negative. By analyzing the responses by gender, we observed differences in the number of elicited emotional terms: females showed significant differences between cakes for 18 emotion terms compared to 8 terms for males. The results obtained support the importance of the emotional profile to understand consumers’ expectations and behavior.